Can Clinical Scenario Videos Improve Dental Students' Perceptions of the Basic Sciences and Ability to Apply Content Knowledge?. Issue 12 (1st December 2015) - Miller, Cynthia Jayne; Metz, Michael James
Abstract : Dental students often have difficulty understanding the importance of basic science classes, such as physiology, for their future careers. To help alleviate this problem, the aim of this study was to create and evaluate a series of video modules using simulated patients and custom‐designed animations that showcase medical emergencies in the dental practice. First‐year students in a dental physiology course formatively assessed their knowledge using embedded questions in each of the three videos; 108 to 114 of the total 120 first‐year students answered the questions, for a 90–95% response rate. These responses indicated that while the students could initially recognize the cause of the medical emergency, they had difficulty in applying their knowledge of physiology to the scenario. In two of the three videos, students drastically improved their ability to answer high‐level clinical questions at the conclusion of the video. Additionally, when compared to the previous year of the course, there was a significant improvement in unit exam scores on clinically related questions (6.2% increase). Surveys were administered to the first‐year students who participated in the video modules and fourth‐year students who had completed the course prior to implementation of any clinical material. The response rate for the first‐year students was 96% (115/120) and for the fourth‐year students was 57% (68/120). The first‐year students indicated a more positive perception of the physiology course and its importance for success on board examinations and their dental career than the fourth‐year students. The students perceived that the most positive aspects of the modules were the clear applications of physiology to real‐life dental situations, the interactive nature of the videos, and the improved student comprehension of course concepts. These results suggest that online modules may be used successfully to improve students' perceptions of the basic sciences and enhance their ability to apply basic science content to clinically important scenarios.